2013
DOI: 10.1371/journal.pone.0067602
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Supraventricular Ectopic Activity Is Indicative of Paroxysmal Atrial Fibrillation in Patients with Cerebral Ischemia

Abstract: BackgroundDetecting paroxysmal atrial fibrillation (PAF) in patients with cerebral ischemia is challenging. Frequent premature atrial complexes (PAC/h) and the longest supraventricular run on 24-h-Holter (SV-run24 h), summarised as excessive supraventricular ectopic activity (ESVEA), may help selecting patients for extended ECG-monitoring, especially in combination with echocardiographic marker LAVI/a’ (left atrial volume index/late diastolic tissue Doppler velocity).MethodsRetrospective analysis from the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 29 publications
2
26
0
Order By: Relevance
“…[9][10][11][12][13][14][15][16][17][18]20,22,23 Several recent studies indicate that Holterdetected frequent APBs, or APBs present on a routine 12-lead ECG, 19,20 are an independent risk factor for stroke or death; previous studies used different thresholds for defining frequent APBs during a 24-hour recording (>100, 16 >218, 14 >228 APBs, 18 or >720 APBs or episodes of atrial tachycardia >20 beats long 15 ). In our study, we found that nearly 50% patients with cryptogenic stroke had an APB frequency >720/24 h, which is potentially clinically important based on the above literature.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18]20,22,23 Several recent studies indicate that Holterdetected frequent APBs, or APBs present on a routine 12-lead ECG, 19,20 are an independent risk factor for stroke or death; previous studies used different thresholds for defining frequent APBs during a 24-hour recording (>100, 16 >218, 14 >228 APBs, 18 or >720 APBs or episodes of atrial tachycardia >20 beats long 15 ). In our study, we found that nearly 50% patients with cryptogenic stroke had an APB frequency >720/24 h, which is potentially clinically important based on the above literature.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been suggested such as BNP level at admission, PAC number, and clinic-radiological scores (e.g. STAF score) [6,20,22,23,24,25,26]. The first-hour risk score in our experience does not appear efficient enough to be included in relevant parameters.…”
Section: Discussionmentioning
confidence: 83%
“…6 in their retrospective cohort study that frequent SVR was not associated with the occurrence of AF. 23 Some prospective 6,22 and retrospective cohort studies 24 have observed that excessive supraventricular ectopic activity (ESVEA) is a significant predictor of the occurrence of AF. In these studies, patients were classified in the ESVEA group if they had either frequent PAC count or SVR.…”
Section: Discussionmentioning
confidence: 99%